Burnout amongst anaesthesiologists: the forgotten issue - Nanyan, Suhaila; Hamdan, Nadiah; Ab Rahman, Najibah Syakirah (Malaysian Society of Anaesthesiologists, 2021)
Burnout is a psychological syndrome that is seen particularly affecting those who are chronically exposed to high levels of stress especially at work. The COVID-19 pandemic had tremendously increased workloads and exposed the healthcare worker to burnout. Risks for burnout include challenges in anaesthetic fields, long working hours, limited resources, professional conflicts, and intrinsic factors such as vulnerable personality. Burnout affects both physical and psychological wellbeing of an individual. As such, it may increase erroneous and legal suits which can be detrimental to both the organisation and the individual. Burnout is managed by socio-psychological training aiming at both individual and organisation levels and it requires multilevel prevention to reduce its incidence among healthcare workers. Detection, treatment, and prevention should be actively carried out to make sure that healthcare workers’ wellbeing is in the optimum state especially during the COVID-19 pandemic.